Spatial and Short Time Variability of Some Soil Properties in a Nursery Garden Experimental Site Irrigated with Low Quality Water - BASARAN, M.; ERPUL, G.; OZCAN, A.U. (Asian Journal of Chemistry, 2010)
Soil salinity can arise eventually whenever irrigation occurs since almost all water consists of some dissolved salts, making drainage crucial to leach salts out of the plant root zone. The development of salination can be hastened in the cases of irrigation with low quality water, especially in arid and semiarid regions. This research was conducted with the aim of determining the spatial and short time variability of the electrical conductivity (EC) together with soil organic matter (OM) and pH in spruce (Picea pungens) nursery garden soils. The site was not tilled for seven years and irrigated with low quality water for a full growth period after it opened to the nursery. A good understanding of short time variability in soil salinity development in the site would help evaluate the problem and take measures promptly if necessary, for producing high quality seedlings. A total of 396 disturbed soil samples were taken with regular intervals of 5 × 5 m and represented the depth of 0-30 cm for four different sampling periods with 45 d time interval in a 40 m × 50 m plot. The soil samplings, which were at May 1st, June 15th, August 1st and September 15th, were made immediately on the same sampling points before the soil tillage applied during the growth. Analysis of variance showed that there were significant differences among the period means of EC and OM. EC and OM values, respectively increased and decreased as the irrigation and soil tillage progressed. pH changes among the periods were not as significant as those of EC and OM. Spatial analysis additionally revealed the development of the soil salinity and the decomposition of organic matter over the study site within a short growth period of 5-month. Especially, in the sampling periods of P3 and P4 the coverage for EC values between 2.74 and 3.25 dS m-1 diminished severely or completely vanished (0.0 and 6.1 and 0.0 and 0.2 %, respectively) and those between 2.50 and 3.75 dS m-1 attained the value of 70.0 %. Spatial coverage of OM between 0.81 and 1.20 attained the value of